2021
DOI: 10.1080/23802359.2021.2006816
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and phylogenetic analysis of the complete chloroplast genome of Lilium concolor Salisb. (Liliaceae) from Jilin, China

Abstract: Lilium concolor Salisb. is a perennial herb with high ornamental and medicinal value in China. The complete chloroplast genome sequence of L. concolor was assembled using high-throughput sequencing data. The chloroplast genome of L. concolor is 152,625 bp in length and consists of large single-copy (82,056 bp) and small single-copy (17,585 bp) regions, and a pair of inverted repeat (26,492 bp) regions. A total of 131 genes were annotated, these included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Lilium pumilum ( L. pumilum ) is not only valuable for having the beautiful bright red ornamental flowers, but also for its strong resistance to disease, cold, drought and salinity, which makes it an unparalleled plant material in Saline-Alkali stress research [ 3 , 4 , 5 ]. Lilium pumilum in this study grows naturally in the heavily salinized and alkalized meadow of Daqing suburb of the Songnen Plain with soil pH as high as 9–10.…”
Section: Introductionmentioning
confidence: 99%
“…Lilium pumilum ( L. pumilum ) is not only valuable for having the beautiful bright red ornamental flowers, but also for its strong resistance to disease, cold, drought and salinity, which makes it an unparalleled plant material in Saline-Alkali stress research [ 3 , 4 , 5 ]. Lilium pumilum in this study grows naturally in the heavily salinized and alkalized meadow of Daqing suburb of the Songnen Plain with soil pH as high as 9–10.…”
Section: Introductionmentioning
confidence: 99%
“…The Lilium pumilum is an excellent plant material because of its high salt tolerance and suitability for alkaline soils. 1 , 2 We analyzed and compared the differential transcriptome of Lilium pumilum without treatment and under 20 mM NaHCO 3 treatment. The results indicated that the expression of the CPC gene was significantly increased under 20 mM NaHCO 3 treatment.…”
Section: Introductionmentioning
confidence: 99%